Efficacy of niclosamide and ivermectin suspension preparations in sheep parasitoses - Victor A. Marchenko; Yury A. Vasilenko; Ivan V. Biryukov; Marat S. Khalikov; Salavat S. Khalikov; Alireza Sazmand (Journal of Advanced Veterinary and Animal Research)
Objective: This study aimed to examine the efficiency of newly formulated drugs based on mech¬anochemical modification of two widely used anthelmintic substances in suspension formulations against the main classes of helminths and parasitic arthropods. Materials and Methods: Solid-phase co-grinding of two substances, i.e., ivermectin (IM) and niclosamide (NS), with licorice extract and sodium succinate was performed in liquid-phase processing to obtain suspension formulations. Drug preparations were administered to the sheep of the experimental groups (5 experimental groups of 8 heads) with different concentrations of active substances, i.e., 3.0, 5.0, and 10.0 mg/kg of body weight (BW) NS and 0.2-mg/kg BW IM. Aqueous suspensions of the original substances in dosages of 0.2-mg/kg BW IM, 10.0-mg/kg NS, and placebo were included as controls. Efficacy of the formulations against gastrointestinal stron¬gyles, Trichuris spp., Moniezia spp., and nasal bot larvae (Oestrus ovis) was assessed in naturally infected sheep by the number of surviving adult parasites post-treatment in the gastrointestinal tract, nasal passages, and sinuses. Results: Formulated suspensions showed an increased solubility of 5.5–13.1 times compared to the original substances. Treatment of sheep with the SusIN-10 drug containing 0.2-mg/kg BW IM and 10.0-mg/kg NS showed 100% efficiency against gastrointestinal strongyles, Moniezia, and nasal bot larvae. Formulations containing 0.2-mg/kg BW IM and 3.0- and 0.5-mg/kg NS could eliminate all of the Trichuris worms. Administration of original substances of IM and NS with rec¬ommended dosages did not result in the adult parasites' complete elimination. Conclusion: Modification of the anthelmintic substances through mechanochemical methods made it possible to create formulations with a targeted spectrum of action, significantly higher water solubility, and optimal parasiticidal activity. [J Adv Vet Anim Res 2024; 11(4.000): 1122-1129]